THE APPLICATION OF MIND MAPPING TECHNIQUE TO INCREASE STUDENTS’ READING COMPREHENSION ACHIEVEMENT AT THE EIGHTH GRADE SMPN 38 PALEMBANG - Silvia Silvia; Jaya Nur Iman; Nike Angraini (Universitas Indo Global Mandiri, 2022)
Reading certainly has many purposes, one of which was by reading people can find out the information, increase knowledge and to expand horizons. Thus the writer tried to explore the use of mind mapping technique to know the significant improvement in students’ reading comprehension achievement in recount text after being taught with mind mapping technique and to know the significant mean difference in students reading comprehension between students who were taught by using mind mapping technique and those who were not. The research design in this study is a quasi-experimental design which the population of this study were students from two classes of eighth-grade of SMPN 38 Palembang which consisted of 32 students of each class. Data collection techniques used in this study were pre-test and post-test. Data were analyzed using t-test (paired sample t-test and independent sample t-test). The outcome of t-obtained in experimental group was higher than t-table (17.201>0.2913). Also, the results of each aspect in experimental group showed that there was improvement. Beside, there was also significant mean difference between students who were taught by using mind mapping technique and those who were not.The findings revealed that teaching reading by using mind mapping technique was effective toward students’ reading comprehension achievement in recount text at the eighth-grade students of SMPN 38 Palembang in the academic year of 2021/2022.